2018
DOI: 10.5222/shyd.2018.064
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Student Nurses Practicing Clinical Practice in a University Hospital

Abstract: Araştırma, kurumda klinik uygulama yapan öğrenci hemşirelerin klinik alanda sorun yaşayıp yaşamadıklarının belirlenmesi, yaşıyorlarsa bu sorunların nedenlerinin belirlenerek düzeltici önlemlerin alınabilmesi için gerekli faaliyetlerin planlanması amacıyla yapılmıştır. YÖNTEM: Çalışma, bir üniversite hastanesinde 2011, 2012 ve 2013 yılı yaz döneminde klinik uygulama yapan hemşirelik lisans öğrencilerine, araştırmacıların hazırladığı anket formu kullanılarak yapılmıştır. Araştırmanın örneklemini 657 öğrenci oluş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Nursing students mostly participate in the process of clinical practice with nurses, and their skills and attitudes are substantially influenced by them (Polat et al, 2018). Participants in our study pointed out the fact that health professionals were behaving inattentively when caring for dying patients.…”
Section: Clinical Experiences Of Terminal Patient' Carementioning
confidence: 95%
See 2 more Smart Citations
“…Nursing students mostly participate in the process of clinical practice with nurses, and their skills and attitudes are substantially influenced by them (Polat et al, 2018). Participants in our study pointed out the fact that health professionals were behaving inattentively when caring for dying patients.…”
Section: Clinical Experiences Of Terminal Patient' Carementioning
confidence: 95%
“…In our study, students reported that they were sent to rooms that had terminal or dead patients for any kind of procedure without being given any proper briefing about them. During clinical education, nursing students obtain preliminary information about the patients they are supposed to care for by consulting nurses or reading patient files before going into the patient’s room (Polat et al., 2018). Aydın and Argun (2010) found in their study that nursing students asked nurses about the patients in the clinic, and expected their support in acquiring the necessary knowledge and skills but most of the time failed to get what they expected.…”
Section: Clinical Experiences Of Terminal Patient’ Carementioning
confidence: 99%
See 1 more Smart Citation
“…Clinical practices are an important part of nursing education. Clinical practices, which complement the theoretical education to form a full and whole nursing education, provide students with the opportunity to learn through doing, to gain individual self‐confidence, self‐respect, professional maturity, and decision‐making and communication skills, and to strengthen these skills (Akman et al, 2019; Alparslan, 2017; Özbasan & Bayram, 2020; Polat et al, 2018; Price, 2019; Şendir et al, 2018; Wang et al, 2019). During clinical practice, it is expected that students will find solutions to the patient's care requirements in a real environment by using their knowledge, attitudes, skills, scientific problem‐solving methods, and assessment of patients' needs in partnership with the patient (Aslan & Akturk, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Nursing education has a very compact education curriculum consisting of theoretical and practical processes, which leads students to have some hardships related to their educational activities as well as the difficulties experienced by them throughout their youth. 12 Specific incidents, such as information overload induced by both theoretical and practical courses, anxiety to harm the patient, concern over confronting with negative responses of patients and patient relatives, the necessity to make rapid decisions in case of the emergencies, challenges in the usage of medical instruments and apparatus, and the potentiality of encountering with the incidence of death, might lead to anxiety and interpersonal problems in students. 13,14 Furthermore, they come across individuals of different ages, gender, culture, and socioeconomic status in challenging conditions, notably in the settings for practicing courses, and interact with them intensively.…”
Section: Introductionmentioning
confidence: 99%